2019
DOI: 10.18805/ijare.a-5141
|View full text |Cite
|
Sign up to set email alerts
|

Diallel analysis of yield and its important components in aromatic rice (Oryza Sativa L.)

Abstract: Eight parents of aromatic rice were crossed in half diallel mating design without reciprocal including parents. The parents were evaluated for eleven different characters. Genetic analysis was done through Griffing’s Method II Model I. Analysis of variance revealed highly significant differences among parents and their crosses for all the characters. Combining ability analysis revealed that gca and sca variance were highly significant for most of the characters studied in F1 generation. Amongst the parental li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 3 publications
2
4
0
Order By: Relevance
“…The comparison of magnitude of general combining ability and specific combining ability variance indicated that the non-additive genetic effects were predominant in the characters, days to 50 % flowering, days to 75% maturity, plant height, branches per plant, number of pods per plant, pod length, number of seeds per pod, biological yield per plant, seed yield per plant, 100 seed weight and protein content, which suggested prime role of non-additive gene action. These results are in line with Gill et al (2014), Prasad and Murugan (2015) and Baradhan and Thangavel (2011) in blackgram, Chuwang Hijam et. al.…”
Section: Resultssupporting
confidence: 90%
“…The comparison of magnitude of general combining ability and specific combining ability variance indicated that the non-additive genetic effects were predominant in the characters, days to 50 % flowering, days to 75% maturity, plant height, branches per plant, number of pods per plant, pod length, number of seeds per pod, biological yield per plant, seed yield per plant, 100 seed weight and protein content, which suggested prime role of non-additive gene action. These results are in line with Gill et al (2014), Prasad and Murugan (2015) and Baradhan and Thangavel (2011) in blackgram, Chuwang Hijam et. al.…”
Section: Resultssupporting
confidence: 90%
“…Sharma and Jaiswal [25] also observed better results for such valuable characters of wheat. Such results had also been confirmed by Padhar et al [26] and Hijam et al [27] in his experiment working with the crop of wheat on different morphophysiological characters.…”
Section: Discussionsupporting
confidence: 73%
“…In diallel analysis, GCA is a function of additive genetic influences, but it may partly include some dominant effects when the gene frequencies are not equal to one half and/or parents are included in the analysis to estimate variances. However, the SCA is the function of non-additive genetic affects that include dominance and epistatic effects (Hijam et al 2018).…”
Section: Combining Abilitymentioning
confidence: 99%